Skin Metastasis from Malignant Ovarian Tumor - A Rare Entity (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Skin metastasis from malignant ovarian carcinoma is rare and seen in only 3% of patients. Hence, we report a case of ovarian cancer with scar metastasis. The patient, a 31 year old woman presented with two skin nodules in the previous laparotomy scar which revealed metastatic papillary serous cyst adenocarcinoma on histopathology. So, it should be considered that ovarian malignancy is not always confined to pelvis and may present with associated skin lesion.J Bangladesh Coll Phys Surg 2015; 33(1): 41-43